2018
DOI: 10.18061/emr.v12i3-4.4951
|View full text |Cite
|
Sign up to set email alerts
|

The lower limit for meter in dance drumming from West Africa

Abstract: Human rhythm perception and sensorimotor synchronization are both constrained by temporal thresholds on several levels. The lower limit for durations that allow for entrainment at the level of metric beat subdivision has been estimated at about 100–120 ms (London, 2002; Repp, 2003). Tempos and subdivision durations reported for American jazz and East African xylophone music performance, however, suggest that the perception of shorter subdivisions within a range of 80–100 ms may well be possible. This paper mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 41 publications
1
11
1
Order By: Relevance
“…The assumption that there exists such a lower limit of duration was not confirmed in this study. Our findings show that the duration of the second sixteenth note in the fast tempo is on average shorter than 80-100 ms, which has been suggested as a lower limit for duration in other genres (Dittmar et al, 2015;Polak, 2017). If the duration patterns found in the present study were 'restricted' by a lower limit of duration, there should either have been an upper limit for the overall tempo, not allowing second sixteenth note durations under a lower limit, or the second sixteenth note should have stabilised around a lower limit of duration at the fast tempo, producing a floor effect that consequently made it more similar to the first and third sixteenth note durations.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…The assumption that there exists such a lower limit of duration was not confirmed in this study. Our findings show that the duration of the second sixteenth note in the fast tempo is on average shorter than 80-100 ms, which has been suggested as a lower limit for duration in other genres (Dittmar et al, 2015;Polak, 2017). If the duration patterns found in the present study were 'restricted' by a lower limit of duration, there should either have been an upper limit for the overall tempo, not allowing second sixteenth note durations under a lower limit, or the second sixteenth note should have stabilised around a lower limit of duration at the fast tempo, producing a floor effect that consequently made it more similar to the first and third sixteenth note durations.…”
Section: Discussionsupporting
confidence: 55%
“…A possible influence of a lower limit for sixteenth note duration was investigated. In the fast tempo (133 bpm), the mean duration for the short second sixteenth note was only 68 ms, which is below the 80-100 ms range suggested as a lower limit for duration in other genres (Dittmar et al, 2015;Polak, 2017). We neither found that rhythmic categories of similar duration merge as a result of increase of tempo, as suggested by Clarke (1985).…”
Section: Resultscontrasting
confidence: 47%
See 2 more Smart Citations
“…Previous tapping studies have rarely used intervals shorter than 250 ms, assuming that nonmusician participants usually cannot tap much faster than that without considerable interference from motor constraints (Povel, 1981;Repp, 2003). By contrast, the threshold for the fastest metric subdivision rate in music performance and perception has been suggested to go down to 125 ms (Repp, 2003), 100 ms (London, 2002), or even 80 ms (Polak, 2017). Basic synchronization or synchronizationcontinuation tapping paradigms thus cannot easily cover the fastest event activity rates found in music when testing the general population.…”
Section: Musicianshipmentioning
confidence: 99%